Desenvolvimento de nanopartículas de óxido de ferro revestidas com glicerol funcionalizado e sua aplicação em remoção de óleos em superfície aquosa - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
The iron oxide nanoparticles have high saturation magnetization, are biocompatible, have low toxicity and their surfaces are easily modified by the insertion of functional groups such as carboxylic acids, surfactants and polymers. The use of functionalized nanoparticles with glycerol molecules that have been modified by reaction of esterification with mono-carboxylic acid is proposed in this work, for their application in the removal of oils in aqueous surfaces. The particles of iron oxide were prepared by the coprecipitation method by alkaline hydrolysis of Fe2+ and Fe3+ in aqueous medium. The precursor used in the coating was obtained by glycerol functionalization with stearic acid via condensation reaction. The coating surfaces of magnetic iron oxides was carried out by two different procedures: (i) addition of glycerol functionalized to the aqueous suspension of the purified iron oxide particles; and (ii) the preparation, purification and drying of the iron oxide particles and subsequent mixing with functionalized glycerol in isopropanol. The functionalized glycerol was characterized by vibrational spectroscopy in the infrared region (FTIR), thermogravimetric analysis (TG) and nuclear magnetic resonance of hydrogen (NMR 1H) and carbon (NMR 13C) and particles of iron oxide were characterized by FTIR, TG, X ray diffraction (XRD), Mössbauer spectroscopy, vibrating sample magnetometer (VSM), transmission electron microscopy (TEM), contact angle measurements and chemical composition by potentiometric titration. The results obtained from the characterization showed formation of the functionalized glycerol. The FTIR spectrum showed absorption bands at 1737 and 1180 cm-1 characteristic of ester group and with the NMR spectra was proposed chemical structure, the sample showed better thermal stability compared to their constituents. The characterizations carried out on samples of iron oxide suggest the presence of inverse spinel cubic structure with lattice parameters and stoichiometry close to magnetite, average diameter of the crystallites of 8.29 nm, saturation magnetization value of 62 emu/g and behavior superparamagnetic. The results obtained by FTIR, thermogravimetric analysis and VSM of nanoparticles coated with glycerol functionalized indicates the presence of organic matter on the magnetic particles. The particles have spherical shape with an average size of 11.17 nm and high hydrophobicity (164°), characteristic of superhydrofobic behavior. These nanoparticles have chemical affinity for oil and are able to move the oil slick on the water surface by applying an external magnetic field, it is possible to completely remove the oil slick approaching a magnet to the stain. These results are promising for the application of these particles in cleaning oil spills on the water surface.
Keywords: Óxido de ferro; Glicerol; Reação de esterificação; Superhidrofóbico; Remoção de óleos; Iron oxide; Glycerol; Esterification reaction; Superhydrophobic; Remove oil; CIENCIAS EXATAS E DA TERRA; QUIMICA::FISICO-QUIMICA